Second Harmonic Generation Covering the Entire Visible Range from a 2D Material–Plasmon Hybrid Metasurface. Issue 16 (20th May 2021) - Ding, Yufeng; Wei, Chengrong; Su, Huimin; Sun, Shuoyan; Tang, Zhiyong; Wang, Zhaona; Li, Guixin; Liu, Dahe; Gwo, Shangjr; Dai, Junfeng; Shi, Jinwei
Abstract: On‐chip coherent light source has always been fascinating and intriguing due to its various potential applications. In the past decades, there has been some progress in the development of chip coherent light (e.g., nanolaser, Bose‐Einstein condensation and nonlinear optical effects). However, these methods strictly depend on materials and extreme experimental conditions, and are usually not tunable. Here, a hybrid structure is designed which combines a chirped surface plasmon metasurface with a monolayer transition metal dichalcogenide (TMDC) to achieve a coherent second harmonic generation (SHG) covering the entire visible light spectrum. Using only finite number of metallic grooves, a continuous resonance tuning is obtained. By translating the metasurface in space, a space‐frequency locking SHG is demonstrated. Although the Q factor of the surface plasmon cavity is low, its near‐field enhancements of both fundamental and SH waves are still obvious. Significantly, the broad linewidth of plasmonic cavity leads to a large degree of overlap between adjacent localized modes, that enables the tuning of the output wavelength continuously at room temperature. Meanwhile, the exciton resonance also plays an important role. This monolithic tunable device demonstrates the potentials of 2D material‐plasmon hybrid metasurface and to construct an efficient broadband tunable on‐chip coherent light source. Abstract : On‐chip coherent light source has always been fascinating and intriguing due to its various potential applications. A hybrid structure is designed which combines a metasurface with a monolayer transition metal dichalcogenide to achieve a coherent second harmonic generation covering the entire visible light spectrum at room temperature. By translating the metasurface in space, a space‐frequency locking broadband SHG is demonstrated.